pVir and Bloody Diarrhea in Campylobacter jejuni Enteritis - Tracz, Dobryan M. (Centers for Disease Control and Prevention, 2005)
The plasmid pVir may play a role in the virulence of Campylobacter jejuni, a leading cause of bacterial gastroenteritis. The pVir plasmid was identified in 17% of 104 C. jejuni clinical isolates studied and was significantly associated with the occurrence of blood in patient stool, a marker of invasive infection. The pVir plasmid was not associated with greater occurrence of diarrhea, fever, pain, vomiting, or need for patient hospitalization. Isolates containing pVir were also associated with the presence of a tetracycline-resistance plasmid, but pVir did not transfer with tetracycline-resistance plasmids to recipient strains of C. jejuni. The association of pVir and bloody stool suggests that pVir may be clinically relevant in C. jejuni infections.